2017
DOI: 10.3390/molecules22020192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aquitaine and Rioja Red Wines: Characterization of Their Phenolic Composition and Evolution from 2000 to 2013

Abstract: Wine chemical analysis was carried out on 194 commercial blended red wines produced by two major wine-growing areas—the Aquitaine (France) and Rioja (Spain) regions—in order to compare the wines of both regions. Anthocyanins and derived pigments, tannins and derivatives were identified and quantified by HPLC-DAD-ESI-MS/MS (high pressure liquid chromatography coupled to diode array detector and mass spectrometry using the electrospray ionization interface). Mean degree of polymerization (mDP) was determined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In particular, berries, red grapes and red wine are important sources of ANCs [6,7]. The main ANCs present in our diet are cyanidin, delphinidin, malvidin, pelargonidin, peonidin, and petunidin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, berries, red grapes and red wine are important sources of ANCs [6,7]. The main ANCs present in our diet are cyanidin, delphinidin, malvidin, pelargonidin, peonidin, and petunidin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the use of monomeric anthocyanins, Quaglieri indicated that wine samples from Rioja (Spain) and Aquitaine (France) were properly discriminated using supplementary markers such as dimers of flavan-3-ols, mean degree of polymerization (mDP), and polymerized pigments [77]. The authors also suggested a general tendency for a decrease in anthocyanin and tannin contents in older wines [77].…”
Section: Profiling Applicationsmentioning
confidence: 99%
“…This condensation reaction occurs in the absence of oxygen, it increases with the temperature and depends on the amount of anthocyanins in the wine [129]. In reality, the color of the resulting wine is modified according to the type of carbo-cation and also to the degree of anthocyanin polymerization [77,124,130].…”
Section: Factors Affecting Polyphenol Concentration and Distribution mentioning
confidence: 99%
“…Therefore, during the last decades, many protocols have been developed to evaluate the structure and the mean degree of polymerization, by applying degradative methods. While the trapping reagent 2-mercaptoethanol has been widely used in the past, the protocols based on the acidic cleavage in the presence of phloroglucinol, followed by an LC-MS analysis are the most commonly used in the last years [ 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], especially when the desired target is the maximal conversion of proanthocyanidins into their constitutive subunit adducts [ 28 ]. The availability of pure standards of the flavan-3-ol phloroglucinol adducts are required for the quantification of acid-catalyzed phloroglucinol degradation products of procyanidins [ 29 ].…”
Section: Introductionmentioning
confidence: 99%